The relationship between levels of income inequality and dental caries and periodontal diseases A associação dos níveis de desigualdade de renda com cárie dental e doença periodontal - Roger Keller Celeste; Johan Fritzell; Paulo Nadanovsky (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
The objective of this study was to evaluate the association between income inequality at a lagged time of 2 and 11 years with two short latency outcomes (untreated dental caries and gingivitis) and two long latency outcomes (edentulism and periodontal attachment loss > 8mm). We used data from the Brazilian oral health survey in 2002-2003. Our analysis included 13,405 subjects aged 35-44 years. Different lagged Gini at municipal level were fitted using logistic and negative binomial multilevel analyses. Covariates included municipal per capita income, equivalized income, age, sex, time since last dental visit and place of residence (rural versus urban). Crude estimates showed that only untreated dental caries was associated with current and lagged Gini, but in adjusted models only current Gini remained significant with a ratio of 1.19 (95%CI: 1.09-1.30) for every ten-point increase in the Gini coefficient. We conclude that lagged Gini showed no association with oral health; and current income Gini was associated with current dental caries but not with periodontal disease. Avaliar a associação entre desigualdade de renda (Gini municipal) defasada em 2 e 11 anos com dois desfechos de curta latência (cárie dentária não tratada e gengivite) e dois de longa latência (edentulismo e perda de inserção periodontal > 8mm). Foram utilizados dados do inquérito brasileiro de saúde bucal em 2002-2003. A análise incluiu 13.405 indivíduos com idades entre 35-44 anos. Foram usados modelos de regressão multinível. Covariáveis incluídas: renda municipal per capita, renda domiciliar equivalente, idade, sexo, tempo decorrido desde a última consulta odontológica e local de residência (rural versus urbano). Estimativas brutas mostraram que apenas cárie dental não tratada estava associada ao Gini (atual e defasado no tempo), mas em modelos ajustados apenas Gini atual manteve uma relação significativa com razão de 1,19 (IC95%: 1,09-1,30) para cada dez pontos de aumento no coeficiente de Gini. Concluímos que o Gini defasado no tempo não mostrou associação com saúde bucal e o Gini atual esteve associado com cárie dentária, mas não com doença periodontal.